Prevalence, prescribing and barriers to effective management of hypertension in older populations: a narrative review. Issue 1 (December 2015) - Alhawassi, Tariq; Krass, Ines; Pont, Lisa
Abstract Objectives Hypertension is the leading modifiable cause of mortality worldwide. Unlike many conditions where limited evidence exists for management of older individuals, multiple large, robust trials have provided a solid evidence-base regarding the management of hypertension in older adults. Understanding the impact of age on how the prevalence of hypertension and the role of pharmacotherapy in managing hypertension among older persons is a critical element is the provision of optimal health care for older populations. The aim of this study was to explore how the prevalence of hypertension changes with age, the evidence regarding pharmacological management in older adults and to identify known barriers to the optimal management of hypertension in older patients. Methods A review of English language studies published prior to 2013 in Medline, Embase and Google scholar was conducted. Key search terms included hypertension, pharmacotherapy, and aged. Results The prevalence of hypertension was shown to increase with age, however there is good evidence for the use of a number of pharmacological agents to control blood pressure in older populations. System, physician and patient related barriers to optimal blood pressure control were identified. Conclusions Despite good evidence for pharmacological management of hypertension among olderpopulations, under treatment of hypertension is an issue. Concerns regarding adverse effects appearcentral to under treatment of hypertension among older populations.